MANAGEMENT OF PYOMETRA WITH FETAL MACERATION IN MIXBREED POMERIAN DOGS WITH OVARIOHYSTERECTOMY - Priharyanthi, Luh Komang Ayu Puteri; Pemayun, I Gusti Agung Gde Putra; Sudisma, I Gusti Ngurah (Buletin Veteriner Udayana, 2023)
Pyometra is a pathological condition in which there is an accumulation of purulent masses in the uterus which affects female animals. Pyometra can occur in animals of any age after the first estrus. This paper reports the case of a two-year-old female Pomerian mixbreed dog with a body weight of 6.4 kg with anamnesa of decreased appetite and enlargement of the abdomen for 3 months with vaginal discharge a week before being examined. A year ago the dog was given depo-progestine therapy and was kept in captivity by being released. Blood hematology examination showed that the dog had leukocytosis accompanied by hyperchromic microstic anemia, ultrasound imaging showed a hypoechoic appearance in the uterine lumen and thickening of the uterine wall and radiographic results showed a radiopaque image which was suspected of the presence of parts of the bone from the destroyed fetus. Dog cases diagnosed with open cervical pyometra accompanied by maceration of the fetus with a fausta prognosis and treated with ovariohysterectomy. Postoperatively given cefotaxime antibiotics intravenously (IV) for two days. on and followed by cefixime orally for 5 five days. On the third postoperative day, he was given an anti-inflammatory in the form of dexamethasone orally for three days and the incision in the abdomen was cleaned with 10% povidone iodine, then enbatic powder was sprinkled every day. On the seventh day after surgery the wound was dry and not inflamed, and the dog was active again. Ovariohysterectomy is the best way to sterilize dogs.